RANCANG BANGUN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN SIMULASI DIGITAL - Hermansyah Hermansyah; Nurindah Dwiyani (Universitas Negeri Padang, 2019)
Interactive Learning Media is a supporting element in generating quality students, students in using learning media whose purpose is to generate students' creativity in learning learning materials in accordance with the provisions of learning, to produce interactive media on Digital Simulation subjects whose presentation consists of text, images and videos learning, so that this attracts students' interest in learning, on digital simulation subjects. Media Interactive Using Macromedia Director 11 needs supporting applications such as Adobe Flash 8, Adobe Photoshop CS3, and Camtasia. Based on the results of the design of the media, it can be concluded that the interactive learning media on the subjects of the X-class Multimedia Digital Simulation have been realized. Interactive Learning Media has been designed later in the feasibility study by a media expert lecturer and two material expert teachers, with an average value of 0.69 and an average material validation value of 0.95 declared valid using the Aiken'V formula and based on the results of the feasibility test the learning media has been declared valid and feasible to be used as a medium of learning in school. Keywords: Designing, Digital Simulation, Interactive Media.